Meeting the market for indigenous birds - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Alphious Moyo, a poultry farmer from Matabeleland North in Zimbabwe, explains why and how he rears local breeds of chicken.